2004
DOI: 10.1068/a36206
|View full text |Cite
|
Sign up to set email alerts
|

A Push – Pull Framework for Modelling the Relocation of Retirees to a Retirement Village: The Australian Experience

Abstract: Although most older people prefer to age in place, nonetheless many do relocate, with a small proportion moving to retirement villages, which provide a purpose designed and built residential and lifestyle environment. Using factor analyses, path analyses, and a push^pull framework, the authors model the decision process of retirees in Australia in order to identify relationships between push^pull factors and predictor variables, using data from a national survey of retirement village residents. The push factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 26 publications
(19 reference statements)
10
114
2
1
Order By: Relevance
“…Predictors of relocation to ordinary housing were living in a large dwelling, recently being alone, living isolated in a rural area, and having lived in the dwelling for at least 10 years. Other frequently reported housing-related reasons for moving within ordinary housing are demanding maintenance of large garden or home (Hansen and Gottschalk 2006;Stimson and McCrea 2004;Sergeant and Ekerdt 2008). Summing up on this review on current literature on relocation in old age, the relation between aspects of health and relocation to institutional settings is well established, but we know less about the influence of aspects of housing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictors of relocation to ordinary housing were living in a large dwelling, recently being alone, living isolated in a rural area, and having lived in the dwelling for at least 10 years. Other frequently reported housing-related reasons for moving within ordinary housing are demanding maintenance of large garden or home (Hansen and Gottschalk 2006;Stimson and McCrea 2004;Sergeant and Ekerdt 2008). Summing up on this review on current literature on relocation in old age, the relation between aspects of health and relocation to institutional settings is well established, but we know less about the influence of aspects of housing.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding relocation to ordinary housing in old age, previous research has identified a diversity of influential aspects. That is, older people do not move because of one but many reasons, with aspects of housing and health highly intertwined (Sergeant and Ekerdt 2008;Stimson and McCrea 2004). A retrospective study among people aged 60-89 who were living alone showed that moves made to another ordinary dwelling were more often motivated by aspects of housing than aspects of health (Oswald et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The narratives in this study explored the daily, lived experience of 16 persons aged 62-89 now living in town having moved from more rural settings and roots. While aging-in-place transitions often look at those moving from a setting into a retirement community (Stimson & McCrea, 2004) or the experiences of the oldest old as they relocate (Löfqvist, Granbom, Himmelsbach, Iwarsson, Oswald & Haak 2013), this study looked at a group that relocated within the same demographic region-moving from a rural farm to a more rural town or city-like setting. After the move, this group still remains dwelling in the community in their own apartments or homes -not in a retirement community or assisted-living facility.…”
Section: Discussionmentioning
confidence: 99%
“…Older persons can be reactive movers (relocating after an event or change in function -such as worsening of health or difficulty in home maintenance (Stimson & McCrea, 2004, 1453. These reactive movers have different outcomes than proactive ones (moves before negative changes occur -such as moving to a smaller or modified home or closer to healthcare; Kang & Pope, 2010).…”
Section: Older Adults' Reasons To Move In the Literature And Definitimentioning
confidence: 99%
“…For instance, a high prevalence of environmental barriers and accessibility problems exist in ordinary houses across industrialized countries [7]. This situation leads older adults to face the complexity of the so called "binary decision" between remaining at home or relocating to alternative forms of housing [8] to enable better consequences for health and well-being. It is only after the work of Wiseman [9] that the process by which older adults relocates or remains in their own homes and communities drove attention in literature [10].…”
Section: Introductionmentioning
confidence: 99%